2009
DOI: 10.2216/08-51.1
|View full text |Cite
|
Sign up to set email alerts
|

Viable cell sorting of dinoflagellates by multiparametric flow cytometry

Abstract: Electronic cell sorting for isolation and culture of dinoflagellates and other marine eukaryotic phytoplankton was compared to the traditional method of manually picking cells using a micropipette. Trauma to electronically sorted cells was not a limiting factor, as fragile dinoflagellates, such as Karenia brevis (Dinophyceae), survived electronic cell sorting to yield viable cells. The rate of successful isolation of large-scale (> 4 litres) cultures was higher for manual picking than for electronic cell sorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…The most common and earliest method of observing phytoplankton is through light microscopy, which is time consuming, labour intensive and demands a high level of taxonomic expertise (Sinigalliano et al 2009;Medlin 2013;McNamee et al 2016). Some species, such as those in Alexandrium Halim, 1960, are relatively featureless and furthermore belong to species complexes, rendering them challenging to identify morphologically (John et al 2005;Anderson et al 2012;John et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common and earliest method of observing phytoplankton is through light microscopy, which is time consuming, labour intensive and demands a high level of taxonomic expertise (Sinigalliano et al 2009;Medlin 2013;McNamee et al 2016). Some species, such as those in Alexandrium Halim, 1960, are relatively featureless and furthermore belong to species complexes, rendering them challenging to identify morphologically (John et al 2005;Anderson et al 2012;John et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, naked dinoflagellates are also difficult to identify from preserved samples. Hence, more efficient approaches to study dinoflagellates have been developed, including the use of scanning electron microscopy (Jung et al 2010), natural fluorescence (Karlson et al 2010), flow cytometry (Sinigalliano et al 2009), high performance liquid chromatography (HPLC) (Gin et al 2006) and molecular methods (Karlson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, individual cells can be diverted from the fluid stream based on entities such as cell morphology, taxonomic position, surface and intracellular protein expression, gene expression, and cellular physiology, and collected into homogenous fractions for further analyses (Ibrahim and van den Engh 2007). It should, however, be stressed that various phytoplankton cells may survive such a process at varying viability, particularly if it is applied to fragile groups such as dinoflagellates Karenia brevis (Sinigalliano et al 2009). Nevertheless, FCM featuring a sorting device has been successfully applied to isolate different phytoplankton taxa (including green algae, diatom, cryptomonads and cyanobacteria) from mixed cultures at a success rate of 80% (Cellamare et al 2010).…”
Section: General Introduction To Flow Cytometrymentioning
confidence: 99%
“…More recently, Doan et al [20] reported the isolation from Singapore waters of microalgal strains for the purpose of biofuel production. However, FACS has been considered to be a technique displaying low efficiency for the isolation of unialgal cultures, especially those of fragile species such as dinoflagellates [21]. Therefore, there is a need to develop simpler and faster methods allowing the isolation of fast-growing strains.…”
Section: Introductionmentioning
confidence: 99%